Relecturas del fracaso: comunidades, género y raza en perspectiva histórica - Alegre Henderson, Magally (2024)
FAILURE. Reversing the Genealogies of Unsuccess, 16th-19th Centuries. This project has received funding from the European Union’s Horizon 2020 Research and Innovation Programme under the Marie Skłodowska-Curie Grant Agreement N° 823998